Implementation of Science and Technology in Volleyball Plyometric Training for High School Students: A Literature Study - Wisnu Prio Nugroho; Agung Wahyudi; Deni Setiawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study critically examines the integration of technology and performance enhancement in plyometric training, particularly in high school volleyball players in Indonesia. The research investigates how technology and scientific advances can be incorporated into the plyometric training methodology to elevate volleyball skills and diminish the risk of injury among young Indonesian athletes. The research method used is qualitative descriptive, with data collection through literature studies from various sources. Primary data sources from several research results are supplemented with some relevant secondary data. The results and conclusions of this study provide valuable insights into how cultural attitudes towards sports science and technology in Indonesia can shape the adoption and effectiveness of advanced plyometric training methods among high school volleyball players. Furthermore, the study evaluates the knowledge and practice of volleyball coaches in Indonesia related to plyometric training and identifies potential gaps in volleyball education and training, with the potential to significantly impact the field of sports science and volleyball training.